Scotland Rising : The Case for Independence. - Hassan, Gerry (Pluto Press, 2022)
A systematic exploration of the arguments for Scottish independence from a sympathetic angle.
Keywords: Self-determination, National -- Scotland.; Home rule -- Scotland.; Scotland -- Politics and government -- 21st century.; Droit des peuples à disposer d'eux-mêmes -- Écosse.; Autonomie locale -- Écosse.; Écosse -- Politique et gouvernement -- 21e siècle.; POLITICAL SCIENCE.; International Relations.; Political Parties.; Political Process.; Constitutions.; Colonialism & Post-Colonialism.; Home rule; Politics and government; Self-determination, National; Scotland; 2000-2099; Electronic books.